Primary extranodal NK/T cell lymphoma of stomach: A case report and review of literature - Prashant Mane; Prashant Ramteke; Anand Singh; Ajay Gogia; Saumyaranjan Mallick (Indian Journal of Pathology and Microbiology)
Extranodal Natural killer/T (NK/T) cell lymphoma nasal type is an aggressive non-Hodgkin lymphoma and has a constant association with Epstein-Barr virus (EBV) infection. Approximately more than 75% cases are located in upper aero-digestive tract, of which stomach is a very rare site. Very few cases of gastric extranodal NK/T cell lymphoma have been reported in the literature. A 22-year-old male patient presented with complaints of abdominal pain and hematemesis. Endoscopy showed a large ulcer in the stomach. Partial gastrectomy done and histopathology showed transmural infiltration by intermediate size atypical lymphoid cells which are immunopositive for CD3, CD56, TIA, EBV-encoded RNA (EBER) and negative for CD4, CD8, CD20. A diagnosis of extranodal NK/T cell lymphoma nasal type was made.